2006
DOI: 10.1093/rheumatology/kei279
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and subclinical inflammation in patients with familial Mediterranean fever and in heterozygous carriers of MEFV mutations

Abstract: Substantial sub-clinical inflammation occurs widely and over prolonged periods in patients with FMF, indicating that the relatively infrequent clinically overt attacks represent the 'tip of the iceberg' in this disorder. Both basal and peak acute phase protein concentrations were greater in MEFV heterozygotes than in wild-type controls, regardless of mutation demonstrating a 'pro-inflammatory' phenotype among FMF carriers. Upregulation of the acute phase response among carriers of FMF may augment their innate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
201
1
28

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(242 citation statements)
references
References 36 publications
12
201
1
28
Order By: Relevance
“…FMF is a disease in which subclinical inflammation can be seen, except during attack times (1,2,19). In our study, we found higher PWV values and frequency of AS in patients with FMF.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…FMF is a disease in which subclinical inflammation can be seen, except during attack times (1,2,19). In our study, we found higher PWV values and frequency of AS in patients with FMF.…”
Section: Discussionsupporting
confidence: 59%
“…Recent studies have shown that subclinical inflammation may continue in some FMF cases, even in the symptom-free periods (1,2). Inflammation is an important cause of the development and progression of atherosclerosis (3).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic AA amyloid deposition is always accompanied by increased SAA production, whether triggered by tissue damage, infection, or abnormal proinflammatory cytokine activity (26)(27)(28)(29)(30). The transgenic mice reported here allowed us to induce expression of the amyloidogenic mouse SAA isoform, SAA2, by oral administration of doxycycline, completely independently of any inflammatory stimulus.…”
Section: Discussionmentioning
confidence: 96%
“…In a large proportion of patients symptom-free intervals of the disease are characterized by subclinical inflammation with overproduction of C-reactive protein (CRP), serum amyloid A (SAA) and other acute-phase reactants [28,29]. During attack-free periods, patients with FMF may still experience arthritis, myalgia, autonomic dysregulation with altered cardiovascular reactivity [30] and other cardiovascular symptoms related to persistent subclinical inflammation [18].…”
Section: Fmf As a Low-grade Inflammatory Disordermentioning
confidence: 99%